INFORMATION TECHNOLOGY-BASED LEARNING (Media Development Applications Quizlet on students in MI DDI Seppange Bone) - Wardana, zakiah (IAIN Ambon, 2019)
pplication quizlet is one of media-based learning android application that can be used to a limited extent to the students, that is, their use by teachers who provided the material is in the form of questions relating to the learning and grating exam questions that will be dihadapai by the students of classes VI MI DDI Seppange Bone. Granting of quizlet is done gradually so that absorption to the students can be more rapid and structured. Use of the media learning is very beneficial to students because it can be developed by entering (input) the subject matter in the form of questions that melingupi an important part of the sub a lesson. Quizlet apps is also a means of contracting the message and information learned. As well as the power tTarik learning using information technology is well designed to help learners in the digest and understand the subject matter. On dasarya this research uses Quasi Experimental Research method, by using the subject of research in the form of a group (class). Class VI MI DDI Seppange taken as the population because, this class was considered qualified and already have knowledge about android-based learning, this can be seen from the quizlet diajuan at the time of pre-test. Variables that are revealed in this research is a study of the response against the application of learning to the students ' quizlet klas VI students taught using quizlet and response application of their learning. Next design research is applied in this study isThe pre-test – post-test control group design.